Independent health screening movement for elderly people through routine health services in Surabaya - Ario Imandiri; Riky Tri Yunardi (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2018)
In the health aspect, it is known that the older a person is, the more health complaints will be. As many as 37.11 percent of the pre-elderly population (45-59 years) had experienced health complaints in the last month, while young elderly (60-69 years) amounted to 48.39 percent, middle aged people (70-79 years) amounted to 57.65 percent and elderly (80-89 years) of 64.01 percent complaining about their health condition. Furthermore, judging from the elderly morbidity rates, namely the disruption of daily activities as a result of health complaints. This activity aims to enable the community, especially the elderly, to overcome their minor illnesses independently, the illness suffered by the elderly group can be overcome or reduced, the use of chemical drugs consumed by the elderly can be reduced in dosage or amount, and the quality of life of the elderly group can be better. The activities carried out were acupressure and herbal counseling, examination of height, weight, nutritional status, blood pressure, examination of blood sugar, cholesterol, gout and therapeutic services for acupuncture to the elderly to overcome or alleviate the disease. Participants present or patients in community service activities in both locations for 12 times were 317 people, of which the majority of participants in this activity were women. Pain is the most common complaint experienced by patients who come to this community service. Many people present in this community service complain that they have sleep disturbances or insomnia. The community feels very happy and welcomes this activity because with this activity the community's knowledge is increasing, they have started practicing acupressure independently as well as herbal medicine for themselves, their families or those around them to cope with the mild ailments experienced. The community becomes aware of their health conditions through examinations, and is more motivated to maintain their life patterns. The perceived complaints, especially pain and sleeplessness disturbances experienced decreased after receiving acupuncture therapy. Especially complaints of pain, where most feel the pain is greatly reduced or immediately disappear after receiving acupuncture therapy even though only one therapy. Only a small number who feel the pain has not diminished, but reduced or disappeared after several acupuncture therapies. Community knowledge related to acupressure and herbal medicine increases, motivation to maintain a good lifestyle increases, and complaints of illness especially pain can be reduced by acupuncture therapy.